Analisis Experiential Marketing, Kepercayaan Merek dan Harga Terhadap Keputusan Pembelian Produk Cat Jotun pada CV. Asia Maju Rantauprapat - Ritonga, Mulkan; Rahma Muti'ah (PT. PENERBIT TIGA MUTIARA, 2023)
The purchase decision is the main goal or purpose of selling a product. This study aims to analyze the influence of marketing experience, price and brand trust on purchasing decisions. This study was conducted using a descriptive quantitative research method with data collection using a research tool in the form of questionnaires distributed directly to respondents. The subjects of this study include consumers who purchased Jotun brand paint products from CV. Asia Maju Rantauprapat during the period specified by the author. Determining the sample size used the purposive sampling technique with a total of 65 consumers. To analyze and analyze the research data, it was carried out using the computer program SPSS version 20 with instrumental testing, classical hypothesis testing, multiple regression analysis and hypothesis testing. Research results show that marketing experience, price and brand trust have a positive and significant impact on purchasing decisions. At the same time, marketing experience, price and brand trust have a positive and significant impact on purchase decisions with a contribution of 0.888 or 88.80% and the remaining 11.20% is influenced by other factors. Other factors were not considered in this study.